Implementasi Pencapaian visi misi dalam peningkatan kualitas Pendidikan berdasarkan instrumen akreditasi satuan Pendidikan (IASP) Tahun 2020 di MIN 2 Kota Bandung - Luthfiana Nurlathifah; Mulyawan Safwandy Nugraha (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Vision and mission are the main foundation for an educational institution in determining the direction and goals to be achieved. Implementing a good vision and mission in education management can have a positive impact on improving the overall quality of education. This is an important aspect in efforts to improve the quality of education in accordance with the 2020 education unit accreditation instrument (IASP). The aim of this research is to describe the implementation of the vision and mission and objectives consisting of developing, disseminating and improving the vision and mission and objectives in accordance with the IASP MI instrument. 2020. This research uses a qualitative approach with descriptive methods to describe things related to achieving the vision, mission and goals in improving the quality of education. Developing the vision and mission of the madrasah is based on preparing a vision and mission that is in accordance with the specific needs of MIN 2 Bandung City. The socialization process at MIN 2 Bandung City is carried out through meetings, brochures/banners, social media and other activities. Socialization is designed to reach all stakeholders evenly and is easy to understand. Improving the vision and mission is used as a basis for continuing or even developing other work programs that are more relevant to the vision and mission and needs of MIN 2 Bandung City. The process of improving the vision, mission and goals at MIN 2 Bandung City was carried out through meetings involving all stakeholders.